SISTEM INFORMASI PENJUALAN FURNITURE JEPARA BERBASIS WEB MENGGUNAKAN METODE DOUBLE MOVING AVERAGE - M. Aufa Alfis Syihab; Anita Andriani; Tanhella Zein Vitadiar; Mahrus Ali (Inovate, 2025)
Mahkota Jati Jepara is a store specializing in various types of teak wood furniture. Currently, the sales data processing system in this store is still done manually. Sales of goods are managed using receipt-based bookkeeping, which leads to difficulties in searching for sales data. This also makes it challenging for company management to obtain information regarding the quantity of goods expected to be sold in the upcoming period. The use of a sales forecasting information system is expected to provide many benefits for companies in managing and processing sales data and sales transactions. By utilizing goods sales data from previous periods, companies can forecast the number of sales that are likely to occur in the future period. With this forecasting system, the store can anticipate the number of sales for the next period. Therefore, a sales information system is needed that uses the double moving average method. This method was chosen because it can help in forecasting sales, so that company leaders can predict market needs and determine the amount of stock that must be provided, so that there is no shortage or excess of furniture sold in the shop. abstranct is a brief summary of a research article, thesis, review, conference proceeding or anydepth analysis of a particular subject or disipline, and is often used to help the reader quickly ascertain the paper purposes. When used, an abstract always appears at the beginning of a manuscript or typescript, acting as the point-of-entry for any given academic paper or patent application. Absatrcting and indexing services for various academic discipline are aimed at compiling a body of literature for that particular subject. Abstract length varies by discipline and publisher requirements. Abstracts are typically sectioned logically as an overview of what appears in the paper. Keywords: Information system, sales forecasting, double moving average, Jepara furniture store.